2013
DOI: 10.1016/j.biocel.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The self-renewal of mouse embryonic stem cells is regulated by cell–substratum adhesion and cell spreading

Abstract: Mouse embryonic stem cells (mESCs) undergo self-renewal in the presence of the cytokine, leukaemia inhibitory factor (LIF). Following LIF withdrawal, mESCs differentiate, and this is accompanied by an increase in cell–substratum adhesion and cell spreading. The purpose of this study was to investigate the relationship between cell spreading and mESC differentiation. Using E14 and R1 mESC lines, we have restricted cell spreading in the absence of LIF by either culturing mESCs on chemically defined, weakly adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 41 publications
6
43
0
Order By: Relevance
“…The discrepancy between previous reports and our current study may result from the fact that most of the total population of tumor cells are probably differentiated tumor cells in those previous reports whereas only undifferentiated TRCs are analyzed in our present study [10]. Our results are consistent with the previous findings that the reduction in FAK activity promotes growth of stem cells [29] while the elevation in FAK activity facilitates their differentiation [30]. These findings may explain why FAK inhibition may not block tumorigenic cell proliferation as the current strategy in clinical trials of the candidate drugs to inhibit FAK does not work [31].…”
Section: Discussionsupporting
confidence: 71%
“…The discrepancy between previous reports and our current study may result from the fact that most of the total population of tumor cells are probably differentiated tumor cells in those previous reports whereas only undifferentiated TRCs are analyzed in our present study [10]. Our results are consistent with the previous findings that the reduction in FAK activity promotes growth of stem cells [29] while the elevation in FAK activity facilitates their differentiation [30]. These findings may explain why FAK inhibition may not block tumorigenic cell proliferation as the current strategy in clinical trials of the candidate drugs to inhibit FAK does not work [31].…”
Section: Discussionsupporting
confidence: 71%
“…(E)]. Although the PLGA was not harmful to the cells it was also not really promoting them, as is obvious from the data shown for polyethersulfone (PES) treated with collagen scaffolds . It was described that mESCs cultivated on PES treated with collagen (PES‐COL) scaffolds presented a significantly higher proliferation rate than the PES or gelatin after 96 h .…”
Section: Discussionmentioning
confidence: 98%
“…Cytoskeleton rearrangement and the Rho-ROCK pathway are critical for both MSC differentiation and ESC self-renewal6566. Here we showed that the Rho-Rock-actin/myosin pathway is important for both cell fusion and entosis in ESCs.…”
Section: Discussionmentioning
confidence: 77%